DAMPAK KEBIJAKAN IZIN PERTAMBANGAN GALIAN C BAGI MASYARAKAT DI DESA PONGKAI ISTIQOMAH KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR 2021 - Wandira, Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Natural resources are a very determining factor for human life. The aim of this research is to determine law enforcement regarding C excavation mining in Pongkai Istiqomah village and to determine the impact on C excavation mining in Pongkai Istiqomah village, XIII Koto Kampar sub-district, Kampar Regency. Type of qualitative research. The data sources used in this research are primary data and secondary data. The results of research on the impact of Excavated C Mining in Pongkai Istiqomah Village, District Cracks and landslides on connecting roads between villages and the loss of recreational areas and some cultural facilities of the local community. Keywords: Impact, Economic, Social